2007
DOI: 10.1038/sj.onc.1210842
|View full text |Cite
|
Sign up to set email alerts
|

The N-methyl-D-aspartate receptor type 2A is frequently methylated in human colorectal carcinoma and suppresses cell growth

Abstract: N-methyl-D-aspartate receptors (NMDARs) are the predominant excitatory neurotransmitter receptors in the mammalian brain. We found that among the three NMDARs examined (NMDAR1, NMDAR2A, NMDAR2B), only NMDAR2A was silenced in colorectal carcinoma (CRC) cell lines at basal line and reactivated by the demethylating agent, 5-aza-2 0 -deoxycytidine. NMDAR2A was expressed in normal colon epithelium, while expression was hardly detectable in colon cancer tissues. Promoter methylation of NMDAR2A was confirmed by bisul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 35 publications
0
29
0
1
Order By: Relevance
“…Causative for the aberrant cellular function of glutamate receptors are changes in genomic sequences, change in the level of expression and aberrant posttranscriptional processing. It has been reported that methylation of gene promoters of NR2B in gastric (Liu et al 2007) and NR2A in colorectal carcinoma cells (Kim et al 2008) inXuenced cancer cells growth, and, as demonstrated by knockout experiments, diminished expression of NR2A and GluR1 subunits and inhibited proliferation of cancer cells (de Groot et al 2008;Watanabe et al 2008). In contrast, the presence of rearranged or mutated forms of glutamate receptor subunits could activate cancer cell growth.…”
Section: Discussionmentioning
confidence: 93%
“…Causative for the aberrant cellular function of glutamate receptors are changes in genomic sequences, change in the level of expression and aberrant posttranscriptional processing. It has been reported that methylation of gene promoters of NR2B in gastric (Liu et al 2007) and NR2A in colorectal carcinoma cells (Kim et al 2008) inXuenced cancer cells growth, and, as demonstrated by knockout experiments, diminished expression of NR2A and GluR1 subunits and inhibited proliferation of cancer cells (de Groot et al 2008;Watanabe et al 2008). In contrast, the presence of rearranged or mutated forms of glutamate receptor subunits could activate cancer cell growth.…”
Section: Discussionmentioning
confidence: 93%
“…By contrast, GluN2A and GluN2B have emerged as potential tumor suppressors. GRIN2A and GRIN2B are genes encoding GluN2A and GluN2B, respectively, and are subject to more extensive promoter methylation in several tumor types compared to normal tissue [143][144][145][146]. GRIN2A and GRIN2B hypermethylation inversely correlated with GluN2A and GluN2B expression levels, and was associated with increased cancer cell proliferation and colony formation in vitro [143,144].…”
Section: Therapeutic Perspectivesmentioning
confidence: 95%
“…85,86 Cancer-specifi c methylation is, however, a rather rare event, and is presumably only recognized in the genes with robust tumor suppressive function. [87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102][103] Methylation of CpG islands for normal genes occurs at random, but hypomethylation is more common in cancer cells than in normal tissues. 104,105 As a result, gene promoter methylation that is related to cancer development or progression is relatively rare, and it is worth further investigation to determine whether these methylated genes can be used as candidate biomarkers and therapeutic targets.…”
Section: Epigenetic Alterations In Gastric Cancermentioning
confidence: 99%